Strategi Pendampingan Usaha Mikro Kecil Minuman Milshake BIIMILK Melalui Media Sosial - Muhammad Afendi; Muhammad Rafif Irhansa; Vera Aulia Rachmawati; Dina Mayasari Soeswoyo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy, particularly as job providers and drivers of local economic growth. However, the main challenges faced by MSMEs include limited market access, business management, and marketing strategies. This study aims to explore the mentoring strategy of the milkshake beverage MSME BIIMILK through social media, with a focus on optimizing digital marketing. The methods used include observation, strategy development, and mentoring and evaluation, involving SWOT analysis, training in creative content creation, and the use of digital ad features such as Ads META. The results show that this strategy successfully increased content posting consistency, audience engagement, and product sales. Mentoring MSMEs through social media has proven effective in improving competitiveness, visibility, and customer loyalty. This study recommends the sustainability of social media utilization to drive business growth for MSMEs in the digital era.